The elements of UML style - Ambler, Scott W., 1966- (Cambridge University Press, 2003)
The elements of UML style is for all developers who create models using the Unified Modeling Language (UML), especially in teams where understandability and consistency are critical. The author describes a collection of standards and guidelines for creating effective UML diagrams that will be concise and easy to understand. This book provides conventions for: class diagrams, use case diagrams, sequence diagrams, activity diagrams, state chart diagrams, collaboration diagrams, deployment diagrams, and component diagrams. The elements of UML style sets the rules for style that will improve your productivity.